Everything sad is untrue : (a true story) - Nayeri, Daniel (Montclair, NJ : Levine Querido, 2020)
At the front of a middle school classroom in Oklahoma, a boy named Khosrou (whom everyone calls "Daniel") stands, trying to tell a story. His story. But no one believes a word he says.
Keywords: Middle school boys -- Juvenile fiction; Immigrants -- Juvenile fiction; Iranian American teenagers -- Juvenile fiction; Families -- Iran -- Juvenile fiction; Truthfulness and falsehood -- Juvenile fiction